Remoções forçadas decorrentes de projetos de desenvolvimento e o direito à moradia digna - Dayse Starling Motta (2016)
The economic development and the progressive urbanization are, nowadays, real scenaries that bring as consequence the marginalization of a vulnerable population, often devoid of the minimum that guarantee a dignified life to them. Such facts have represented a signifícant increase in development projects (particularly infrastructure works) that require the involuntary movement of thousands of families, usually reaching those in an unfavorable economic situation, who do not have their most basic rights guaranteed, requiring positive actions of the Public Authorities, including the Judiciary Power. It is necessary to universalize the effectiveness of human rights, ensuring full citizenship and provide adequate care to those who have not reached yet decent living conditions, either through more effective public policies (attributed primarily to the executive and legislative functions), or ensuring access to fair legal system (through the jurisdictional function). Among these rights that are the minimum necessary for a decent life, there is the right to adequate housing. In this context, it is up to us to analyze the roles and contributions of the Judiciary Power, whose purpose is the social pacifícation. This Power must ensure in the performance of its jurisdictional function not only the entrance to their organs, but mostly the access to the fair legal system, respecting the vulnerability of those involved and, especially, treading paths to ensure the proper handling of conflicts presented to them. And with that look, to ensure access to the fair legal system, that it's being developed the "Conciliation Judicial Program to the Humanized Removal and Resettlement of Families of the Ring Road of Belo Horizonte and BR 381/North", running in the Judicial Section of Minas Gerais. The program aims to implement the Constitutional policy of respect for human dignity, deconstructing the traditional procedure of removal and resettlement. The humanization of this process entails respect for human rights associated with the interests of the community, performing a joint and coordinated action of several public and private institutions with society, in order to the recognition of the right to the city and a dignified life for ali.